2017
DOI: 10.1016/j.ejvs.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Patient Demographics, Anatomy, Comorbidities, and Peri-operative Planning on the Primary Functional Maturation of Autogenous Radiocephalic Arteriovenous Fistula

Abstract: Of all the variables, cephalic vein and radial artery diameter are independently associated with the primary functional maturation of RCAVFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 25 publications
(23 reference statements)
2
29
2
Order By: Relevance
“…15,19,31,33 In addition, tourniquet-derived preoperative vein diameters are used in some studies 14,15,22,29 but not in others. 17,21,33,34 Tourniquet-derived measurements have been shown to increase outflow vein measurements by >30% in some series, 37 and perioperative assessment after brachial plexus block has demonstrated that size increases from preoperative tourniquet-derived diameters up to an additional 0.96 mm. 38 As a result, a wide range of vessel size criteria have been proposed for radiocephalic access creation, from a 2-mm artery and 3-mm cephalic vein 22 to a radial artery diameter >1.65 mm and cephalic vein diameter >1.55 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,19,31,33 In addition, tourniquet-derived preoperative vein diameters are used in some studies 14,15,22,29 but not in others. 17,21,33,34 Tourniquet-derived measurements have been shown to increase outflow vein measurements by >30% in some series, 37 and perioperative assessment after brachial plexus block has demonstrated that size increases from preoperative tourniquet-derived diameters up to an additional 0.96 mm. 38 As a result, a wide range of vessel size criteria have been proposed for radiocephalic access creation, from a 2-mm artery and 3-mm cephalic vein 22 to a radial artery diameter >1.65 mm and cephalic vein diameter >1.55 mm.…”
Section: Discussionmentioning
confidence: 99%
“…38 As a result, a wide range of vessel size criteria have been proposed for radiocephalic access creation, from a 2-mm artery and 3-mm cephalic vein 22 to a radial artery diameter >1.65 mm and cephalic vein diameter >1.55 mm. 34 Finally, there is marked heterogeneity in vein diameter reporting among studies. Although a minimum vein diameter in the outflow tract is used in some, 19,21,22,29 a significant number use perianastomotic values, 15,17,20,31,32,36 including four of five randomized controlled trials examining the utility of preoperative duplex ultrasound vs physical examination for access creation.…”
Section: Discussionmentioning
confidence: 99%
“…2) The impact of multiple variables on the FM of RCAVF has been extensively investigated, and to date it has become apparent that certain variables might impact FM. 3) However, conflict regarding their independent impact, association and causal link is persistent, and despite conclusive evidence of a few series, this is negated by others and recent guidelines remain inconclusive. 4) This has been attributed to the fact that the majority of such outcomes are derived from cohort studies, and despite all efforts they could be subjected to selection, performance and conclusion bias or could lack randomisation.…”
Section: Introductionmentioning
confidence: 99%
“…According to the National Kidney Foundation, Centre for Medicare and Medicaid Services (CMS) and Dialysis Patient Citizens, arteriovenous fistula (AVF) remains the access of choice (gold standard) for dialysis patients. 1,2) However, an increase in the incidence of end-stage renal disease in association with longer life expectancy has escalated the demand for more reliable, functional, cost effective and durable AVF. 3,4) This has subsequently resulted in the amplification and deployment of different endovascular and open salvage techniques for the management of AVF complications and their longevity.…”
Section: Introductionmentioning
confidence: 99%